FAMILY THEREVIDAE - Rodrigues, Paula Fernanda Motta; Calhau, Julia (Zootaxa, 2016)
This catalogue presents the Colombian fauna of stiletto flies (Diptera: Therevidae). According to available literature, only four species, distributed in three genera, are registered to this country, Ataenogera brevicornis (Bromley, 1934), Brachylinga punctifrons (Kröber, 1914), B. xanthoperna Irwin and Webb, 1991 and Chromolepida pruinosa (Coquillett, 1904).